The relevance of the Belém do Pará Summit to implement the Amazon Cooperation Treaty - Salinas Montes, Carlos A. (2024)
The IV Belém Summit in Pará, Brazil, held in August 2023, brought together the leaders of the member countries of the Amazon Cooperation Treaty Organization (OTCA) to discuss a new sustainable agenda for the region. The Amazon was the focus of attention due to its global importance as the largest watershed and the most extensive and diverse tropical forest on the planet. The Summit highlighted the importance of strengthening OTCA as the only intergovernmental coordination mechanism to implement the agreed presidential agenda. The Belém Declaration established priorities for effective regional cooperation, including sustainability, environmental preservation, and inclusive development. The challenges to be faced include the efficient management of OTCA, the improvement of governance and positioning as a center for regional and international technical and political cooperation. The successful implementation of the agreed agenda will require the commitment of the Amazon countries and the active participation of all stakeholders, especially indigenous peoples and local communities.